Metal accumulation and its effect on leaf herbivory in an allopolyploid species Arabidopsis kamchatica inherited from a diploid hyperaccumulator A. halleri. Issue 2 (1st December 2020) - Shimizu‐Inatsugi, Rie; Milosavljevic, Silvija; Shimizu, Kentaro K.; Schaepman‐Strub, Gabriela; Tanoi, Keitaro; Sato, Yasuhiro
Abstract: Excessive amounts of metal ions in soil are toxic for most plant species, yet metal can also facilitate plant survival by elemental defense against herbivores and pathogens. Zinc and cadmium hyperaccumulation in Arabidopsis halleri is known to be effective for the defense against natural enemies. The allotetraploid species A. kamchatica, derived from A. halleri and a non‐hyperaccumulator A. lyrata, has a lower hyperaccumulation level of zinc than A. halleri, but its significance for elemental defense remains unknown. In this study, we evaluated the accumulation levels of zinc and cadmium in the allotetraploid compared with its diploid progenitors, and evaluated the contribution of metal treatments to anti‐herbivore resistance under field conditions. The accumulation level of zinc in A. kamchatica was intermediate between the progenitors, but that of cadmium was lower than in both diploid progenitors. The elemental defense of A. kamchatica and A. halleri was supported by a field experiment comparing the herbivory level between a control group and metal‐supplemented plants. Moreover, the effect of elemental defense was lower in A. kamchatica than in the hyperaccumulator progenitor A. halleri, which is consistent with the metal accumulation level. This result reveals that the allotetraploid plant inherited its hyperaccumulating ability from one progenitor as an advantageous trait but at an intermediate level. Abstract : Zinc and cadmium hyperaccumulation in Arabidopsis halleri is known to be effective for defense against natural enemies. The allotetraploid species A. kamchatica, derived from A. halleri and a non‐hyperaccumulator A. lyrata, has a lower hyperaccumulation level of zinc than A. halleri, but its significance for elemental defense remained unknown. In this study, we have found that the ability to defend themselves using toxic metals is inherited in the allotetraploid, but both of the metal accumulation level and the defensive effect in A. kamchatica are intermediate compared to A. halleri and A . lyrata .